Uji Aktivitas Antioksidan Ekstrak Bunga Telang (Clitoria ternatea L.) Dengan Metode DPPH (2,2 DIiphenyl 1-1 Pickrylhydrzyl) - Yulia Kusumanti; Eldesi Medisa Ilmawati; Usti Fina Hasanah Hasibuan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: The current state of Indonesian society in general is concerning. People want to use motorized vehicles to travel instead of walking or cycling. All this leads to an increase in the amount of unfastened radicals inside the body. Antioxidants are needed to overcome the risks of unfastened radicals. Indonesia is very rich in herbal sources consisting of numerous flora, one of which is the telang flower (clitoria ternatea l.) which is thought to have antioxidants. Activity: To determine the antioxidant activity of telang flower (Clitoria ternatea L.) by dpph (2,2-Diphenyl 1-1 Picrylhydrazyl). Method: Antioxidant activity test can be done by using several kinds of methods, namely dpph, abts, etc..Results: Classification of secondary metabolite compounds found in flower telang (Clitoria ternatea L.) includes alkaloids, flavonoids, quinones, saponins, tannins, and steroids with the technique used with the DPPH test. The results of the test sample for the extract of telang flower (Clitoria ternatea L.) have an IC50 of 356.65 ppm and are classified as very weak. The ic50 value assessment of the ethanol extract of telang flower (Clitoria ternatea L.) with methanol as solvent has a value of 95.Conclusion: Assessment of antioxidant activity can be assessed from IC50. The IC50 assessment of the flower telang (Clitoria ternatea L.) has obtained different results, namely the weak and strong IC50. This can be influenced by the maximum wavelength used, as well as the storage temperature of the extract of a plant. In addition, a good solvent, namely methanol, is needed in measuring the IC50 of telang flower (Clitoria ternatea L.) using DPPH.